Public Key Cryptography – PKC 2007
DOI: 10.1007/978-3-540-71677-8_29
|View full text |Cite
|
Sign up to set email alerts
|

Fast Batch Verification of Multiple Signatures

Abstract: Abstract. We propose an efficient batch verification of multiple signatures generated by different signers as well as a single signer. We first introduce a method to generate width-w Non-Adjacent Forms (w-NAFs) uniformly. We then propose a batch verification algorithm of exponentiations using w-NAF exponents, and apply this to batch verification for the modified DSA and ECDSA signatures. The performance analysis shows that our proposed method is asymptotically seven and four times as fast as individual verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Note that the ambiguities arising out of h > 1 and/or q > n can be practically solved by appending only a few extra bits to standard ECDSA signatures [1,4]. Consequently, our assumptions are neither too restrictive nor too impractical.…”
Section: Assumptionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Note that the ambiguities arising out of h > 1 and/or q > n can be practically solved by appending only a few extra bits to standard ECDSA signatures [1,4]. Consequently, our assumptions are neither too restrictive nor too impractical.…”
Section: Assumptionsmentioning
confidence: 96%
“…ECDSA*, a modification of ECDSA introduced by Antipa et al [1], permits an easy adaptation of Naccache et al's batch-verification protocol for DSA. Cheon and Yi [4] study batch verification of ECDSA* signatures, and report speedup factors of up to 7 for same signer and 4 for different signers. However, ECDSA* is not a standard, and is thus unacceptable, particularly in applications where interoperability is of important concern.…”
Section: Introductionmentioning
confidence: 97%
“…Cheon and Yi [4] reported that in addition to requiring less computation time, a batch-verification technique generally performs approximately 4.8 times faster than individual verifications. Assuming that a vehicle needs to verify a safety message set consisting of n safety messages simultaneously, SCPP's batch-verification procedure uses the following two steps.…”
Section: Batch Verificationmentioning
confidence: 98%
“…As remarked in [36], fast validation of vehicular messages is crucial for a wide deployment of VANETs in practice. To meet this requirement, we use a batch-verification technique similar to the one shown in [36] and [37]. When a vehicle receives safety messages from other vehicles in the group maintained by R i whose public key is w i , it runs the following VBVerify algorithm to check the validity of these safety messages.…”
Section: ) Batch Verificationmentioning
confidence: 99%
“…Using the batch-verification technique requires only two (rather than 2n) bilinear map operations. In addition to saving in bilinear map computation, the above batch verification performs approximately 4.8 times faster than the individual verifications [37]. 6) Tracing: Malicious entities (vehicles) may exist in VANETs.…”
Section: ) Batch Verificationmentioning
confidence: 99%